Ferromagnetic order in diamond-like carbon films by Co implantation. (7th January 2016) - Gupta, Prasanth; Williams, Grant; Markwitz, Andreas
Abstract: We report the observation of ferromagnetic order in diamond-like carbon (DLC) films made by mass selective ion beam deposition and after low energy implantation with Co ions. Different Co fluences were studied with a peak concentration of up to 25% at an average Co implantation depth of 30 nm. The saturation moment per Co atom (0.2–0.3 μ B ) was found to be strongly dependent on temperature and it was significantly lower than that reported in bulk cobalt or cobalt nanoparticles (1.67 μ B per Co atom). The observed magnetic moment cannot be attributed to ferromagnetic nanoparticles as no evidence for superparamagnetism was detected. The magnetic order observed may be due to Co bonding in DLC possibly leading to dilute ferromagnetic semiconductor behaviour with an inhomogeneous distribution of cobalt atoms. Raman spectroscopy measurements showed that Co implantation resulted in an increase in the sp 2 clustering with increasing Co fluence. Thus, our results show that Co implantation into DLC films increases the graphitic properties of the film and leads to magnetic order at room temperature.